(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Facies succession of the Oligocene terrigenous sequences from a seccar of Piedmont Tertiary Basin (between Ovada and Cassinelle, Alessandria) are here described and their significance discussed. The palaeogeographic evolution of the area results to be controlled by a synsedimentary tectonics. In the Early Oligocene, a generalised vertical mobility affected the region which, as a consequence, was splitted in some blocks with a differential tectonic behaviour by tensive lineaments; that is testified by a widesprcad continental facies characteristic of a high energy environment (lower pare of "Formazione di Molare"). Successively, ali the area subsided, and the sea transgressed over it (upper part of "Formazione di Molare"). During the Late Oligocene subsidence acted differentially along synsedimentary faults and the deeper portions are individuated; which became location of relatively deep marine deposition ("Marne di Rigoroso"). The intense tectonic activity was responsible for the deposition of large conglomeratic and arenaceous bodies interbedded within the hemipelagic sequences (in the areas with precocious and intense drowning).